Studies on Some Physico-Chemical Characteristics of Ground Water Used in Some Rural Areas of Surat District (Gujarat) - Patel, S.R.; Desai, K.K. (Asian Journal of Chemistry, 2016)
A physico-chemical study of the ground water of some villages of Surat, India has been made for parameters as temperature, pH, conductivity, TDS, total hardness, calcium, magnesium, chloride, sulphate, total alkalinity, nitrate, fluoride, iron, sodium and potassium. It was found that these water samples have higher TDS, chlorides and alkalinity than the permissible limits.